2006
DOI: 10.1002/ajhb.20549
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratio and hand-grip strength in German and Mizos men: Cross-cultural evidence for an organizing effect of prenatal testosterone on strength

Abstract: The ratio of the length of the second and fourth digits (2D:4D), a putative proxy of prenatal testosterone (PT), is correlated with measures of physical fitness. The relationship between the organizing effect of PT on physical fitness is likely to arise as a response to intrasexual male competition for females. Physical strength is also likely to be important in intrasexual conflict, but nothing is known concerning the relationship between 2D:4D and strength. The strength of an individual is strongly influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
112
5
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 41 publications
7
112
5
8
Order By: Relevance
“…16 Studies report a negative correlation of right hand 2D:4D ratio with HGS in men of Hani ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Studies report a negative correlation of right hand 2D:4D ratio with HGS in men of Hani ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly negative association was found between 2D:4D and HGS in Caucasian and Mizo men but other studies, controlling for ethnicity, found no significant correlation in men or women. 16,17 Such correlations may be ethnicity specific. Moreover, digit ratios do not seem to be correlated with grip strength in women.…”
Section: Introductionmentioning
confidence: 99%
“…In order the identification of 2D:4D finger ratio to be a criterion in talent auditions, more research should be conducted on children and 2D:4D. Most of the studies regarding 2D:4D include adults (Beaton et al, 2011;Fink et al, 2006;Paul et al, 2006;Zhao et al, 2012), adolescents (Peeters et al, 2013), only a single physical fitness parameter (Manning et al, 2000;Manning and Hill, 2009;Folland et al, 2012) and groups of athletes in a single branch of sports (Bilgiç, 2016;Voracek et al, 2010;Kilduff et al, 2011;Tamiya et al, 2012;Manning, 2002;Manning, 2009;Bennet et al, 2010;Sudhakar et al, 2013;Kociuba et al, 2017). The aim of this study is to determined correlation between the right hand finger ratio (2D:4D) and the parameters of anthropometric and physical fitness in male and female children aged 10 -12.…”
Section: Introductionmentioning
confidence: 99%
“…Besides being effective on many areas such as a person's psychological condition (Manning, 2008;Manning et al, 2011;Acar and Eler, 2018), risk of developing cancer or having a heart attack (Manning, 2008;Fink, et al, 2006), sexual preference, mathematical and verbal intelligence, finger ratio is also an indicator of a person's predisposition for sports (Tester and Campell, 2007). Low 2D:4D is accepted to be related to high performance in many sports and 2D:4D has been suggested to have a negative correlation with physical performance in many studies (Manning and Taylor, 2001;Manning, 2002;Paul et al, 2006;Bennett et al, 2010;Hill et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation